Innovation as a success factor in tourism: empirical evidence from western Austrian cable-car companies - Mayer, Marius (ERDKUNDE, 2009)
With demand for winter sport stagnating cable-car innovations implemented by tourism entrepreneurs can serve as a means of differentiating the product to meet new consumer preferences. Taking into consideration their nature, spatial diffusion and distribution, the most important cable-car innovations in Austria are examined within a systematic empirical analysis. The quantitative approach is supplemented by qualitative analysis of expert interviews. Cable-cars are suitable examples for innovations in tourism but they are not tourist innovations in the narrow sense. The early adopters of innovations are able to realize certain advantages in contrast to laggards. But it should be clear that important investments in infrastructure are not sufficient to meet increasing customer expectations. A modern cable-car system represents a constitutive basic factor for ski tourism which is taken for granted by the guests. In general, cable-cars today do not constitute a tourist attraction per se any more. Incremental innovations establish too quickly as nearly ubiquitous standards. But it is possible to generate added value for customers in form of innovative features provoked by especially innovative cable-cars.